Mykologische Untersuchungen zur Pilzflora des Hühnerkammes im Vergleich mit der humanmedizinischen Mykopathologie - Gründer, Susanne; Justus Liebig University Giessen (My University, 2004)
Die klassische Epidermomykose (Trichophytie, Tinea) des Huhns ist der 'Hühnerfavus'. Der ursächliche Erreger ist der zoophile Dermatophyt Trichophyton gallinae. Literaturangaben lassen vermuten, daß der Pilz heutzutage in mitteleuropäischen Ländern nur noch selten vorkommt. Die vorliegenden Untersuchungen wurden durchgeführt, um Informationen über das gegenwertige Vorkommen von Trichophyteon gallinae, anderen Dermatophyten, speziellen Schimmelpilzen und Hefen bei Hühnern in diversen kommerziellen Haltungsformen zu bekommen. Dazu wurden 599 ausgewachsene Hühner in zwei unterschiedlichen geographischen Regionen Deutschlands (Hessen und Schleswig-Holstein) zunächst klinisch untersucht, danach wurden Hautproben durch Kürettage von den Hühnerkämmen genommen. Die Haltungsformen umfaßten 3 Legebatterien (Probezahl n=79), 6 Bodenhaltungen (n=69), 12 Freilandhaltungen (n=320) und eine Volierenhaltung (n=32).

Mycologic examinations about the fungal flora of the comb of chickens and comparison of this flora with the human mycopathology. Favus (Ringworm) is a typical epidemomycosis (trichophytia, tinea) of chickens. The causative agent is the zoophilic dermatophyte Trichophyton (T.) gallinae. Literature data suggest that this fungus hardly exists in poultry of central European countries. Attempts are made in this study, to collect information on the prevalence of T. gallinae, other fungi and yeasts in commercial chickens kept in various forms of housing. For this purpose, 500 aduld chickens living in two different geographic locations in Germany (Hessen and Schleswig-Holstein) were clinicaly examined and scrapings from the combs were collected. A total of 500 samples were obtained from chickens which are maintained in different housing systems. These include 3 chicken flocks kept in batery cages (n=79 samples), 6 chicken flocks maintained on deep litter (n=69 samples), 12 chicken flocks kept on free outdoor range (n=320 samples) and 1 flock kept in a voliere system (n=32 samples).
Keywords: ddc:630